TRANSPLANTASI LAMUN Thalassia hemprichii DENGAN METODE JANGKAR DI PERAIRAN TELUK AWUR DAN BANDENGAN, JEPARA - Wulandari, Dwi; Riniatsih, Ita; Yudiati, Ervia (977-2407769)
The seagrass bed is a coastal ecosystem which have an important role for the coastal environment. The seagrass beds are vulnerable with changes of water environmental conditions. The decrease of seagrass beds area in the world are the result from environmental stresses both of natural and impact of human activities. Transplantation is one way of to rehabilitate the condition of seagrass beds were damaged. The purpose of this research was to determine the survival rate and the rate of growth of transplanted seagrass Thalassia hemprichii with anchor method at Teluk Awur and Bandengan Waters Jepara. The method used in this research was field experimental method. Determination of sites using purposive random sampling method. The research was conducted at two stations are Teluk Awur Water as Station I and Bandengan Water as Station II. Each station divided into 3 plots of observation. The environmental parameters were taken are: salinity, temperature, current velocity, depth, nitrate, phosphate, dissolved oxygen, organic matter, composition and grain size of the substrate. The results showed that the survival rate of seagrass transplants at Teluk Awur water was higher when compared to the survival rate of seagrass transplants at Bandengan water. The survival rate of seagrass transplants at Teluk Awur water have a range of of 38,89% to 41,67%, while the survival rate of seagrass transplants at Bandengan water have a range of 20,97% to 23,15%. The average range growth rate of seagrass transplants at Teluk Awur water was 0,13 cm/day to 0,16 cm/day, while the average range growth rate of seagrass transplants at Bandengan water was 0.16 cm/day up to 0.17 cm/day.